Genealogical Etymology and its Use in Persian Language - Alireza Fouladi (مطالعات زبانی و بلاغی)
Geneology, in its modern sense, has emerged from the ideas of Friedrich Nietzsche and Michel Foucault. Nietzsche attempted to attribute the cause of the existence of moral generations to behaviors of social classes. Foucault, while tracking Nietzsche's work, created the concept of Geneology based on the recognition of the systematic breakdowns of generations with an inverted approach from today to the past. Although Nietzsche has been influenced by Philology in this field, the Genealogical Etymology has not yet emerged. The present article is intended to introduce this knowledge. The research approach based on Foucault’s genealogy model, has been selected the identification of breaking points in current lexical generations. It is discussed in the theoretical basics of the Genealogical Etymology, about the equivalent value of relative languages and their internal value, as well as in the practical basics of this knowledge, about the separating how of the lexical generations and then' their dynasties and families. Finally, for example, we have done Geneology of "آتش" vocabularic generation. In summary, the word has seven dynasty and each dynasty, has one to a few family, whose relationship is still unknown.